Personality Development Analysis of Jean Louise Scout In Harper Lees To Kill a Mockingbird (1960) And Go Set a Watchman (2015) - Nugraha, Wiweko Aksan; Kurnia, Fabiola D; Mustofa, Ali (International Journal for Educational and Vocational Studies, 2020)
The study was aimed to analyze the two continued novels from the personality development of Jean Louise Scout in Harper Lees two novels, How to Kill a Mockingbird and Go Set a Watchman from emotional, cognitive, moral, and religious aspect using Jacques Lacan psychoanalysis theory. It was qualitative study and data of the study were taken from the two novels elements such as words, phrases, sentences, quotes, monologues, and the dialogs while the supporting data collected from books, journals, thesis as the preliminary studies and essay which relevant to the novel analysis. Based on data analysis, the result shows that in studying one literary work there are three interrelated element has to be concerned and it cannot be separated from one to another. The author writes the social phenomena into the literary work because it is a reflection of society and it gives moral values to the reader or to the society. Therefore, sociological approach is utilized in this study. Another finding was found that as a member of society, an individual cannot be separated from its societys tradition in which they should behave in a good manner to be the good member of society as well as in family.